What We Learned From The Three Waves of The Covid-19 Pandemic In Indonesia - Hesty Mustika Dewi; Ratna Dwi Wulandari (Universitas Aisyah Pringsewu, 2023)
Background: The COVID-19 pandemic, which has hit the entire world, has so far experienced three peaks of rising cases, and Indonesia is no exception. However, no research discusses the factors that play a role in the three peaks of this wave, especially in Indonesia. Objective: To find out which of the factors affect the increase in the cumulative incidence and rate of deaths due to COVID-19 in the first, second and third waves in Indonesia. Methods: This research is analytic observational, using secondary data. The data is processed using cross-tabulation. Results and Conclusion: Mask use compliance factor, regardless of the correct use of masks, did not have much impact on reducing the cumulative incidence and the percentage of deaths due to COVID-19 in all three waves. Likewise, the increase in social distancing compliance factors, regardless of mobility restrictions and population density, did not affect the decrease in cumulative incidence and the percentage of deaths due to COVID-19. The percentage of the population at high risk was shown to be positively correlated with the percentage of deaths but not with the cumulative incidence. While the population density factor has a relationship with the cumulative incidence and percentage of deaths due to COVID-19 in almost all waves.Abstrak: Latar Belakang: Pandemi covid-19 yang melanda seluruh dunia, hingga saat ini telah mengalami tiga puncak gelombang kenaikan kasus, tak terkecuali di Indonesia. Namun, belum ada penelitian yang membahas faktor faktor apa saja yang berperan dari ketiga puncak gelombang ini, khususnya di Indonesia Tujuan: Untuk mengetahui manakah faktor yang mempengaruhi terjadinya kenaikan insiden kumulatif dan persentase kematian akibat covid-19 pada gelombang pertama, kedua dan ketiga di Indonesia. Metode: penelitian ini bersifat observasional analitik, dengan menggunakan data sekunder. Data diolah dengan menggunakan tabulasi silang. Hasil dan Kesimpulan: Faktor kepatuhan pemakaian masker, tanpa memandang faktor pemakaian masker yang benar, tidak banyak memberi dampak terhadap penurunan insiden kumulatif maupun persentase kematian akibat covid-19 di ketiga gelombang. Begitu juga dengan peningkatan faktor kepatuhan social distancing tanpa memandang pembatasan mobilitas serta kepadatan penduduk tidak banyak berpengaruh pada penurunan insiden kumulatif serta persentase kematian akibat covid-19. Faktor persentase penduduk berisiko tinggi terbukti berkorelasi positif dengan persentase kematian, namun tidak dengan insiden kumulatif. Sedangkan faktor kepadatan penduduk memiliki hubungan dengan insiden kumulatif maupun persentase kematian akibat covid-19 pada hampir semua gelombang.